Oraşul medieval transilvan: un exerciţiu de genealogie a inovaţiei şi a modernizării sociale - Ungurean, Ştefan (Calitatea Vieții, 2009)
This article focuses on the way in which the concept of “path dependency” can be used in analyzing the social modernization phenomenon. Social modernization depends, historically speaking, on the history of the city – defined, as Weber does it, as illegitimate type of domination. Knowing the medieval Transylvanian city (in this case, Brasov), allows us to understand certain modernity characteristics and could explain nowadays’ Romanian regional disparities. The key-concept that we propose is genealogy.